Pengaruh Sistem Alat Tapping Box dan Kesadaran Wajib Pajak Restoran Terhadap Tingkat Kepatuhan Pembayaran Pajak Daerah di Kota Bandar Lampung - Aria Ruandi Mahibbat; Nurdiono Nurdiono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of implementing the Tapping Box Tool System on payment compliance in increasing local taxes in Bandar Lampung City and to determine the level of awareness of restaurant taxpayers in Bandar Lampung City on payment compliance in increasing regional tax revenues in Bandar Lampung City. Methods used used in this research is a quantitative approach. The data collection method is a questionnaire with the measurement scale used, namely the Likert scale. The conclusion of this research is that the implementation of the Tapping Box Tool System has a significant effect on the level of compliance with regional tax payments in Bandar Lampung City. So this research accepts hypothesis one (H1) which has been proposed and taxpayer awareness has a significant and significant effect on the level of compliance with regional tax payments in Bandar Lampung City. So this research accepts the second hypothesis (H2) that has been proposed.